Rhetoric of violence. On eristic methods used by Stalinist courts in the perspective of Chaïm Perelman’s theory - Pieniążek, Marcin (Filozofia Publiczna i Edukacja Demokratyczna, 2017)
Eristic methods of the Stalinist courts are a phenomenon, on the one hand, well-documented, yet on the other hand, insufficiently explored from the theoretical perspective. They can be understood as forms of violence occurring in the language of the judicial discourse participants (judges, prosecutors), aimed at the total elimination of political opponents. The article is an attempt to characterise these methods using the conceptual instruments, developed by Chaïm Perelman and presented in the work Logique juridique. Nouvelle rhétorique and L’empire rhétorique. Rhétorique et argumentation. What weighs in favour of using Perelman’s theory are its roots in the abundant achievements of the ancient rhetoric. More importantly, however, one of the main objectives of Perelman was the development of the modern theory of legal argumentation, including judicial one. In this regard, the views of the philosopher are adopted as a counterpoint in the rhetorical analyses of the abuses of the Stalinist courts discussed on the example of the Trial of the Sixteen and the Trial of General A. E. Fieldorf „Nil”.